2005
DOI: 10.1101/gad.327005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of junD in cardiac hypertrophy and heart failure

Abstract: Cardiac hypertrophic stimuli induce both adaptive and maladaptive growth response pathways in heart. Here we show that mice lacking junD develop less adaptive hypertrophy in heart after mechanical pressure overload, while cardiomyocyte-specific expression of junD in mice results in spontaneous ventricular dilation and decreased contractility. In contrast, fra-1 conditional knock-out mice have a normal hypertrophic response, whereas hearts from fra-1 transgenic mice decompensate prematurely. Moreover, fra-1 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
5
39
0
1
Order By: Relevance
“…26 Studies with junD Ϫ/Ϫ mice and cells have revealed new physiological functions of JunD, including regulation of spermatogenesis, control of cell senescence and apoptosis, prevention of renal cell proliferation and hyperplasia, regulation of lymphocyte proliferation and differentiation, inhibition of tumor angiogenesis, and cardiac hypertrophy. [11][12][13][27][28][29] Our studies of junD Ϫ/Ϫ mice have provided direct evidence that JunD functions as a profibrogenic factor in diseased liver. Interestingly, this is in contrast with the apparently antifibrogenic function that JunD has in the kidney following partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies with junD Ϫ/Ϫ mice and cells have revealed new physiological functions of JunD, including regulation of spermatogenesis, control of cell senescence and apoptosis, prevention of renal cell proliferation and hyperplasia, regulation of lymphocyte proliferation and differentiation, inhibition of tumor angiogenesis, and cardiac hypertrophy. [11][12][13][27][28][29] Our studies of junD Ϫ/Ϫ mice have provided direct evidence that JunD functions as a profibrogenic factor in diseased liver. Interestingly, this is in contrast with the apparently antifibrogenic function that JunD has in the kidney following partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although AP-1 is up-regulated during the early stages of the hypertrophic response, FOSL1 (fra-1) gene deletion failed to affect the hypertrophic response to chronic pressure overload or sustained ␤-adrenergic stimulation (9). In contrast, fra-1 overexpression resulted in premature decompensation.…”
Section: Traf3ip2 (Traf3 Interacting Protein 2; Previously Known As Cmentioning
confidence: 99%
“…3) (339). JunD, although dispensable for development, has been shown to be involved in muscle differentiation (11) and has been implicated in the development of cardiac hypertrophy (263). The JunD phosphorylation and docking site sequences (Tables 1 and 2) are conserved in a shorter splice form of JunD, ⌬-JunD, which lacks the N-terminal menin interaction domain, suggesting that both JunD splice forms are under the control of JNK phosphorylation (339).…”
Section: Transcription Factors As Jnk Substratesmentioning
confidence: 99%